Drosophila Ectoderm-expressed 4 modulates JAK/STAT pathway and protects flies against Drosophila C virus infection - Huang, Zongliang; Wang, Wei; Xu, Pengpeng; Gong, Shangyu; Hu, Yingshan; Liu, Yan; Su, Fang; Anjum, Khalid Mahmood; Deng, Wu-Min; Yang, Suping; Liu, Jiyong; Jiao, Renjie; et al. (Frontiers in Immunology, 2023)
Sterile alpha and HEAT/Armadillo motif-containing protein (SARM) is conserved in evolution and negatively regulates TRIF-dependent Toll signaling in mammals. The SARM protein from Litopenaeus vannamei and its Drosophila orthologue Ectoderm-expressed (Ect4) are also involved in immune defense against pathogen infection. However, the functional mechanism of the protective effect remains unclear. In this study, we show that Ect4 is essential for the viral load in flies after a Drosophila C virus (DCV) infection. Viral load is increased in Ect4 mutants resulting in higher mortality rates than wild-type. Overexpression of Ect4 leads to a suppression of virus replication and thus improves the survival rate of the animals. Ect4 is required for the viral induction of STAT-responsive genes, TotA and TotM. Furthermore, Ect4 interacts with Stat92E, affecting the tyrosine phosphorylation and nuclear translocation of Stat92E in S2 cells. Altogether, our study identifies the adaptor protein Ect4 of the Toll pathway contributes to resistance to viral infection and regulates JAK/STAT signaling pathway.